Implementasi Manajemen Risiko Keamanan Bersumber UUD 1945 dan NKRI Pada Tahap Eksplorasi Minyak dan Gas Di PT Chevron - Ridwan Zaidaan; Edy Soesanto; Mochamad Raka Putra Basarah (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2024)
Oil and gas exploration is the process of searching, evaluating, and identifying locations beneath the Earth's surface that have the potential to contain oil and natural gas. In Indonesia, the exploration of oil and gas is regulated by Law Number 22 of 2001 concerning Oil and Natural Gas, which